Evidências simultâneas de ausência de genotoxicidade e anti genotoxicidade de Zizyphus joazeiro Mart. (raspa-de-juá) usando o ensaio do micronúcleo - Públio, Juliana Yoshida (2012)
The therapeutic activity of Ziziphus joazeiro Mart. (raspa-de-Juá) has been demonstrated from some studies, such as, antifungal, antibacterial, antipyretic and antioxidant properties. The aim of this research was to evaluate the mutagenicity of glycolic extract of Z. joazeiro Mart. (GEZJ) barks using the micronucleus assay in bone marrow of mice (heterogenetic Swiss albinus Unib: SW). The interaction between GEZJ and the genotoxic effects of doxorubicin (DOX) was also analysed. Experimental groups were evaluated after 24-48 h of treatment with N-Nitroso-N-ethylurea (NEU) and DOX (positive controls), NaCl (a negative control) and GEZJ (250-2,000 mg.Kg-1). Anti-mutagenic assays were carried out using the GEZJ in combination with these positive controls (GEZJ+NEU and GEZJ+DOX). The frequency of micronucleated polychromatic erythrocytes (MNPCEs) was significantly different (p < 0.05) between (i) the positive and negative control treatments, (ii) the positive controls and animals treated with GEZJ and (iii) animals treated with positive controls (NEU or DOX) and GEZJ combined with these positive controls. There was no mutagenicity (clastogenicity/aneugenicity) observed in GEZJ regardless of the dose and time, but a variable response was observed among genders of mouse. The anti-mutagenic effects of GEZJ suggest a potential protective mechanism against DOX-induced genotoxic effects.